Il “palazzo per un viniziano”. Villa La Luna a San Domenico di Fiesole: una biografia architettonica - Mazzanti , Beatrice (Opus Incertum, 2019)
A systematic study of the archival documentation of villa La Luna in San Domenico in Fiesole has been carried out for the first time. The villa was built in the 1470s in the territory outside the city of Florence for the Venetian citizen Girolamo Martini, and recorded by Giorgio Vasari as a work by Giuliano da Sangallo. This research reconstructs the form and substance of the residence in the 15th century by analysing archive documents and historiographical and iconographical material beginning from the second half of the 19th century back through to the mid-16th century. In this four-century journey through life at the villa, the patrons and those they employed have been brought to light, as well as some important phases in the transformation of the building, effectively represented with technical drawings showing the hypothetical original structure and the subsequent alterations.